A Theoretical Basis for a Multilateral Tax Treaty - Hynes, Robert (Curtin University, 2022)
This thesis argues that a multilateral tax treaty should be developed to combat base erosion and profit erosion in a more effective way because: 1 The bilateral architecture of the current international tax treaty network, and the individual domestic tax rules it has generated, are significant facilitators (rather than inhibitors) of BEPS 2 A more effective multilateral tax treaty for reducing BEPS should be developed by the OECD as a de facto global tax coordination body.